2008
DOI: 10.1529/biophysj.107.124743
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Flexible Random-Coil Dextran Polymers Measured in Anisotropic Brain Extracellular Space by Integrative Optical Imaging

Abstract: There are a limited number of methods available to quantify the extracellular diffusion of macromolecules in an anisotropic brain region, e.g., an area containing numerous aligned fibers where diffusion is faster along the fibers than across. We applied the integrative optical imaging method to measure diffusion of the fluorophore Alexa Fluor 488 (molecular weight (MW) 547) and fluorophore-labeled flexible random-coil dextran polymers (dex3, MW 3000; dex75, MW 75,000; dex282, MW 282,000; dex525, MW 525,000) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 45 publications
6
57
0
Order By: Relevance
“…The D value we measured for TR-BSA (Table 1) agreed well with protein correlation predictions for monomeric BSA (8.6–9.2 × 10 −7  cm 2 /s)30 as well as previous experimental measurements31. The experimental D and d H for TR-Dex70 (as well as the other two dextrans) were also well in line with prior estimates using nonlysine fixable dextrans28 as well as correlation predictions32. Taken together, the results confirmed the stability and monodisperse nature of all four tracers, yielding a 2.7–12.4 nm range of tracer d H to be used for nasal vascular permeability measurements (Table 1).…”
Section: Resultssupporting
confidence: 87%
“…The D value we measured for TR-BSA (Table 1) agreed well with protein correlation predictions for monomeric BSA (8.6–9.2 × 10 −7  cm 2 /s)30 as well as previous experimental measurements31. The experimental D and d H for TR-Dex70 (as well as the other two dextrans) were also well in line with prior estimates using nonlysine fixable dextrans28 as well as correlation predictions32. Taken together, the results confirmed the stability and monodisperse nature of all four tracers, yielding a 2.7–12.4 nm range of tracer d H to be used for nasal vascular permeability measurements (Table 1).…”
Section: Resultssupporting
confidence: 87%
“…More flexibility in the IgG hinge region may allow certain IgGs to diffuse slightly better through the narrow brain ECS than expected based on the length of their hydrodynamic axes, e.g. studies with significantly larger dextrans have shown that conformational flexibility allows random coil polymers larger than the ECS width to extracellularly diffuse by processes such as reptation[44]. Another possible contributing factor to our AF488-IgG’s high λ value may be related to charge effects.…”
Section: Discussionmentioning
confidence: 97%
“…The IOI method has been extended to encompass regions of anisotropic grey matter (417). Following an earlier study with the RTI-TMA method (314) (Section IV.A.5), the IOI method was used to make measurements in the ECS of the anisotropic molecular layer of the isolated turtle cerebellum using the small fluorophore Alexa Fluor 488 (AF, 0.547 kDa) and fluorophore-labeled dextrans, with molecular mass of 3, 75, 282 and 525 kDa (417) (Table 3).…”
Section: Methods Of Measurementmentioning
confidence: 99%